Efficient and Versatile Catalytic Systems for the N-Methylation of Primary Amines with Methanol Catalyzed by N-Heterocyclic Carbene Complexes of Iridium - Toyooka, Genki; Tuji, Akiko; Fujita, Ken-ichi (Synthesis, 2018)
Efficient and versatile catalytic systems were developed for the N-methylation of both aliphatic and aromatic primary amines using methanol as the methylating agent. Iridium complexes bearing an N-heterocyclic carbene (NHC) ligand exhibited high catalytic performance for this type of transformation. For aliphatic amines, selective N,N-dimethylation was achieved at low temperatures (50–90 °C). For aromatic amines, selective N-monomethylation and selective N,N-dimethylation were accomplished by simply changing the reaction conditions (presence or absence of a base with an appropriate catalyst). These findings can be used to develop methods for synthesizing useful amine compounds having N-methyl or N,N-dimethyl moieties.
Keywords: iridium; carbene ligands; hydrogen transfer; amines; methylation